Medical management pathways for Cushing’s disease in pituitary tumors centers of excellence (PTCOEs) - Giustina, A; Uygur, MM; Frara, S; Barkan, A; Biermasz, NR; Chanson, P; Freda, P; Gadelha, M; Haberbosch, L; Kaiser, UB; Lamberts, S; Laws, E; et al. (Springer, 2025)
Purpose: A recent update of consensus guidelines for the management of Cushing’s disease (CD) included indications for medical therapy. However, there is limited evidence regarding their implementation in clinical practice. This study aimed to evaluate current medical therapy approaches by expert pituitary centers through an audit conducted to validate the criteria of Pituitary Tumors Centers of Excellence (PTCOEs) and provide an initial standard of medical care for CD. Methods: Based on the activities of nine international PTCOEs between 2018 and 2020, we evaluated patients under medical treatment and their biochemical control rates. Results: The median number of active patients with CD per center was 117 (35–279), with a median number of 10 new patients with CD managed annually in the endocrinology units of PTCOEs (4–42). The median percentage of patients with CD receiving medical treatment was 13.3% (4.8–82.9). Ketoconazole was the most frequently used drug, with a median rate of usage of 26.5% (5-66.7) of those receiving medical therapy. The median rates of metyrapone and pasireotide use were 17.2% (0–50) and 9.3% (0-51.7), respectively. For cabergoline and osilodrostat, therapy, the median rates of use were 2.8% (0-33.3), and 1.7% (0–25), respectively. Combination therapy was reported to be utilized in 13.6% (0-45.5) of medically treated patients. Mifepristone was used in a single center, representing 1.1% of its medically treated patients. Overall, the median control rate in patients with CD receiving medical treatment was 75% (10–100). Conclusion: Adrenal steroidogenesis inhibitors were the most commonly used medications amongst the centers. Despite the use of combination therapy, up to 25% of patients did not achieve disease control even in PTCOEs, highlighting the need for either more efficient combination therapies or novel therapeutic options.